Development of a Local System for Civil Protection and Civil Defence Using the Resources of Voluntary Fire Brigades - Skrabacz, Aleksandra (Roczniki Nauk Społecznych, 2026)
Voluntary fire brigades operating at the municipal level guarantee an acceptable level of safety for local authorities and communities. The potential of community fire protection units, including their human, organizational, and operational resources, is utilized in rescue, educational-cultural, and preventive activities. These features of volunteer fire brigades have enabled their inclusion as entities in the civil protection and civil defence system. In order to properly carry out the wide range of tasks assigned to voluntary fire brigades, it is necessary to cooperate with municipal authorities, state fire service units, and residents who join the ranks of voluntary fire brigades. The article offers a quantitative and qualitative analysis of the potential of volunteer fire brigades, pointing to challenges (in terms of threats and opportunities) that may affect the functioning of volunteer rescue services in the civil protection system at the local level in the years to come.